2013
DOI: 10.1021/la3050835
|View full text |Cite
|
Sign up to set email alerts
|

Partial Coalescence of Sessile Drops with Different Miscible Liquids

Abstract: Using computer simulations in three spatial dimensions, we examine the interaction between two deformable drops consisting of two perfectly miscible liquids sitting on a solid substrate under a given contact angle. Driven by capillarity and assisted by Marangoni effects at the droplet interfaces, several distinct coalescence regimes are achieved after the droplets' collision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Finally, one can solve the thickness of the thin film h by combining Eqs. (4) and (8). As anticipated, the various scaling laws are such that the thickness is independent of time…”
Section: Results and Scaling Lawssupporting
confidence: 56%
See 2 more Smart Citations
“…Finally, one can solve the thickness of the thin film h by combining Eqs. (4) and (8). As anticipated, the various scaling laws are such that the thickness is independent of time…”
Section: Results and Scaling Lawssupporting
confidence: 56%
“…This slowing down is markedly different from the "delayed coalescence," observed when two sessile drops of miscible liquids come into contact. [6][7][8][9][10] Rather than coalescing, the drop of the larger surface tension was found to pull the other drop at constant velocity over the substrate. Such a constant velocity suggests that the surface tension gradient remains constant and localized where the two fluids meet, at least during the initial stages of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karpitschka and Riegler observed that when two chemically different sessile droplets come within close contact of each other, they do not coalesce immediately but remain separated in a temporary state of noncoalesence. Based on hydrodynamic analyses of the phenomenon, Borcia and Bestehorn deliberated that the surface tension gradient causes Marangoni flow at the neck region where the two droplets are connected, eventually producing a temporary dewetting of states between the two droplets. Yerushalmi‐Rozen et al also reported that mixtures composed of two kinds of oligomers on a solid surface undergo phase separation which is driven by the difference in surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…The instability wavelength at the onset is λ o ≈ 0.45 mm in figure 11 The driving forces of the coalescence and coarsening of the droplets are on the one hand a reduction of interfacial area and on the other hand differences in the overall species concentration in neighboring droplets. This concentration difference corresponds to a surface tension difference that causes the droplet with lower surface tension to flow towards the droplet with higher surface tension [70][71][72][73][74][75][76][77][78]. Since the concentration differences in neighboring droplets are very likely small, a coalescence delay [73][74][75][76][77][78] does not occur.…”
Section: Two-dimensional Simulationsmentioning
confidence: 99%